Моделирование ламинарно-турбулентного перехода в компрессорной решетке - Деревянко, А. И.; Ершов, Сергей Владимирович (НТУ "ХПИ", 2011)
The Low-Reynolds turbulence model with the kinetic energy production limiter is considered. The laminarturbulent transition method is implemented in the solver FlowER-Y on the base of the k–ω SST model. Calculation results were compared with experimental data for gas flow in compressor blade cascade. It is shown that the Low-Reynolds modification of the k–ω SST model allows an approximate simulation of some effects in a transitional flow.
Keywords: турбомашины; моделирование течений; модели турбулентности; модель Уилкокса